Design and hydraulic analysis of a multiphase pump. Issue 1 (January 2021) - Yao, R; Cao, J W; Ahn, S H; Guo, B; Xiao, Y X; Wang, Z W
Abstract: With the development of offshore oilfields, foreign companies and research institutes spend plenty of resources on the research of subsea multiphase pump. The helico-axial multiphase pump is generally characterized by large flow and high head unit, and has the advantages of good anti-sand performance, simple structure and small volume. This paper introduces the design of the two-stage compression unit model of a helico-axial multiphase pump by using CFD method. A numerical simulation of full three-dimensional flow field is carried out to study the blade number and the wrap angle influence on external characteristics of the pump. The optimum design combination is selected as the research object and the influence of different inlet gas volume fraction on the internal and external characteristics of the pump is discussed. The design and hydraulic analysis of the multiphase pump can provide a basis for its use in the offshore oil-gas gathering and transportation system.